(3GdCOhjI GdeVehfI GdJi JSei HGdJLQjI GdWHjIs - (3Mfjf Hf ESMGb , CHh RjO Mfjf Hf ESMGb GdYHGOj,J (B260 (3g` s
(3ChdgG (B:s
(3bGd LGdjfhS Ef GdfGQ GdJi CJJ Ydi Gdgjcd CMQbJ cJH Gdedc hGMJQbJ ddCWHGA eY Pdc cJH cKjQI LOkG s
(3BNQgG (B:s
(3hEf hbY EdjfG HYO Pdc COhjI aGVdI MLQjI CKHJfGgG ai BNQ gPg GdebGdI Ef TGA Gddg JYGdi s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B287 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B87s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdWHs